Loss-of-function variant in the LRR domain of SLITRK2 implicated in a neurodevelopmental disorder - Afsar, Tayyaba; Fu, Hongxia; Khan, Hammal; Ali, Zain; Zehri, Zamrud; Zaman, Gohar; Abbas, Safdar; Mahmood, Arif; Alam, Qamre; Hu, Junjian; Razak, Suhail; Umair, Muhammad (Frontiers in Genetics, 2024)
Background: Neurodevelopmental disorders (NDDs) are characterized by different combinations of intellectual disability (ID), communication and social skills deficits, and delays in achieving motor or language milestones. SLITRK2 is a postsynaptic cell-adhesion molecule that promotes neurite outgrowth and excitatory synapse development.In the present study, we investigated a single patient segregating intellectual disabilities, and significant neuropsychological issues inherited in a rare X-linked fashion were recently reported. Whole-exome sequencing (WES) and data analysis revealed a novel nonsense variant [c.789T>A; p.(Cys263*); NM_032539.5; NP_115928.1] in exon 5 of the SLITRK2 gene (MIM# 300561). 3D protein modeling revealed substantial changes in the mutated SLITRK2 protein, which might lead to nonsense-medicated decay (NMD).This study confirms the role of SLITRK2 in neuronal development and highlights the importance of including the SLITRK2 gene in screening individuals presenting neurodevelopmental disorders.